Solar assisted heat pump desalination system - Hawlader, Mohammad Nurul Alam; Dey, P K; Sufian, Diab; Chang, Y C (ELSEVIER, 2004)
This paper describes a novel system of solar assisted heat pump desalination. A single effect desalination unit has been designed and fabricated, and it is connected to an existing solar assisted heat pump. The system consists of a compressor, condenser, evaporator, solar evaporator-collector, desalination chamber, feed tank, vacuum pump and distillate collection unit. A vacuum pump is connected to the desalination chamber. A spray nozzle has been used to generate droplets of feed water in the desalination unit. The feed water has been preheated before being sprayed by the nozzle. The desalination unit incorporates both falling film evaporation and flash distillation concepts.A series of experiment has been conducted on the system under different operating and meteorological conditions of Singapore. The effects of feed temperature and flashing have been investigated. The performance ratio and the coefficient of performance (COP) have been evaluated. The performance ratio (PR) obtained from the experiments ranges from 0.77 to 1.15 and COP of the system was found to vary between 5.0 and 7.0.